2004
DOI: 10.1111/j.1462-2920.2004.00634.x
|View full text |Cite
|
Sign up to set email alerts
|

Acetoclastic and hydrogenotrophic methane production and methanogenic populations in an acidic West‐Siberian peat bog

Abstract: Sites in the West Siberian peat bog 'Bakchar' were acidic (pH 4.2-4.8), low in nutrients, and emitted CH4 at rates of 0.2-1.5 mmol m(-2) h(-1). The vertical profile of delta13CH4 and delta13CO2 dissolved in the porewater indicated increasing isotope fractionation and thus increasing contribution of H2/CO2-dependent methanogenesis with depth. The anaerobic microbial community at 30-50 cm below the water table produced CH4 with optimum activity at 20-25 degrees C and pH 5.0-5.5 respectively. Inhibition of methan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
231
3
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 297 publications
(257 citation statements)
references
References 95 publications
11
231
3
7
Order By: Relevance
“…stordalenmirensis' SSU rRNA gene are present in the non-redundant nucleotide database from 33 locations across four continents (Fig. 3) comprising up to 75% of detected archaeal sequences in some instances 17 . These locations include temperate, subtropical and marine habitats spanning a wide range of physicochemical conditions (Supplementary Tables 8 and 9).…”
Section: Resultsmentioning
confidence: 99%
“…stordalenmirensis' SSU rRNA gene are present in the non-redundant nucleotide database from 33 locations across four continents (Fig. 3) comprising up to 75% of detected archaeal sequences in some instances 17 . These locations include temperate, subtropical and marine habitats spanning a wide range of physicochemical conditions (Supplementary Tables 8 and 9).…”
Section: Resultsmentioning
confidence: 99%
“…This difference between soils and peat bogs might be the result of a much lower contribution of methanogenic Euryarchaeota, which can contain GDGT I in high amounts (Koga et al, 1993), to the total microbial community in soils. In contrast to peat bogs, where methanogens (Euryarchaeota) can comprise up to 36% of the total microbial community (Kotsyurbenko et al, 2004), little data are available on the abundance of Euryarchaeota in soils. Molecular ecological studies of soils have mainly revealed sequences belonging to the non-thermophilic Crenarchaeota and have rarely revealed clones belonging to the Euryarchaeota (e.g.…”
Section: Isoprenoid Gdgts I-ivmentioning
confidence: 99%
“…DeLong et al, 1994;MacGregor et al, 1997;Schleper et al, 1997;Vetriani et al, 1999;Jurgens et al, 2000;Karner et al, 2001;Keough et al, 2003), peat bogs, wetlands and soils (e.g. Buckley et al, 1998;Ochsenreiter et al, 2003;Sizova et al, 2003;Kotsyurbenko et al, 2004) and the deep subsurface (Takai et al, 2001). Despite being ubiquitous, only a limited number of archaeal cultures is available, mostly thermophiles and methanogens, one 'symbiont culture' of a mesophilic Crenarchaeota: Cenarchaeum symbiosum, an archaeon living in symbiosis with the marine sponge Axinella mexicana (Preston et al, 1996) and a nitrifying crenarchaeote isolated from a sea aquarium (Kö nneke et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, acetoclastic methanogenensis contributed approximately 70 % of total methane production in freshwater environments because of low sulfate concentration [21,22]. In this study, the fragments affiliated with Methanosaeta and Methanomicrobiales accounted for 21 and 27 % of all fragments averagely.…”
Section: Distribution and Phylogenetic Analysismentioning
confidence: 80%